ПОЛНЫЙ СИНДРОМ КАВАСАКИ В ДЕТСКОЙ ПРАКТИКЕ КАК ОСЛОЖНЕНИЕ COVID-19 - Мусатова, Людмила Александровна; Краснова, Людмила Ивановна; Бакулина, Ирина Вячеславовна; Теплухина, Олеся Владимировна (FORCIPE, 2022)